Analisis Peningkatan Keterlibatan Siswa Melalui Pendekatan TPACK Dalam Proses Belajar Mengajar - Putri Andini; Zahara Br. Karo; Herawati Herawati; Syahrial Syahrial (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This research presents an analysis of increasing student engagement through the use of TPACK (Technological Pedagogical Content Knowledge) in the teaching and learning process. Using a qualitative approach, this research explores the implementation of TPACK by teachers and its impact on student interaction, active participation, and academic achievement. Findings show that the implementation of TPACK facilitates the appropriate use of technology in learning contexts, enriches students' learning experiences, and encourages more active student involvement in the learning process. This analysis also reveals challenges and opportunities related to the integration of TPACK in curriculum and teacher training. In conclusion, this research highlights the importance of TPACK in supporting student-centered learning and offers practical insights for educators in planning learning that is innovative and relevant to student needs.